Regional developments: Middle East and North Africa [in 2025 GFPR] - Kurdi, Sikandra; Hassan, Ganna; Jovanovic, Nina; Steinhuebel-Rasheed, Linda (International Food Policy Research Institute, 2025)
Over the past 50 years, food and agricultural policy in the Middle East and North Africa has alternated between the dual aims of prioritizing efficiency and economic growth, and ensuring national security through food self-sufficiency and broad-based provision of staple commodities. This chapter summarizes the historical trends in policies and outcomes as the region moved from heavy state interference to a period of liberalization, first examining agricultural production and related policies and then consumers and food and nutrition policy, before concluding with emerging policy issues and research priorities.